Watermark redundancy using sudoku - Ahmad Khalid, Shamsul Kamal (2018)
In today’s world, designer of a watermarking system had to constantly faced with determined attacks to remove copyright information from a watermarked cover image. Due to these attacks, a watermark could be seriously corrupted and not detectable anymore or the watermark could be so noisy that it’s proof of ownership is questionable. Many redundant watermarking systems have been proposed to address these problem. However, they are not designed with adequate redundancies to protect the watermark, and existing metrics merely disregard noisy watermarks for proof of ownership. In this thesis, a new watermark redundancy using Sudoku watermarking is proposed. In Sudoku watermarking, an 81-digit Sudoku “serial” numbers are embedded into a cover image. These numbers are represented in the form of series of small image tiles, constructed from a given watermark. The 81 tiles were divided into halves or more and hidden into the cover image using multiple schemes (composite schemes) that would complementarily protect the watermark from different attacks. During retrieval process, the image tiles are converted back to its Sudoku number. Due to attacks, some numbers may be missing. However, as other numbers will likely remain protected due to the composite schemes, these missing numbers can be regenerated back to its full Sudoku key by using a Sudoku solver. As a result, the image tile usage, the composite schemes and the Sudoku solver collaboratively enable verification of watermark for noisy and missing watermark. Using the classic 9 × 9 Sudoku puzzle, the proposed approach has been implemented and tested with Salt and Pepper, Cropping, Gaussian, compression, Poisson, speckle, low pass filter, high pass filter and contrast attacks on standard test images. The approach is found to be able to improve detection by 19% as compared to existing methods when attacked by random cropping and by 10% improvement with Salt and Pepper attack. For the rest of the attacks, the average correct number of tiles recovered (NoT) and correct Sudoku key (CoK) are 75% and 100%, respectively. The result indicates that the new layers of redundancy improve detection of watermark. Furthermore, the binary metric (CoK) can be used to standardize evaluation of watermarking systems.